Analisis Sektor Basis dan Hubungannya Dengan Pertumbuhan Ekonomi Kota Tomohon - Ples, Yedija Agustina; Jocom, Sherly Gladys; Rori, Yolanda Pinky Ivana (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2026)
Regional economic growth is greatly influenced by the existence of leading sectors, particularly the base sector. However, in Tomohon City, there has been no in-depth study of the base sector, its competitiveness, and its contribution to the local economy. This study aims to identify the base sector in Tomohon City, measure its competitiveness, and analyze the relationship between the growth of the base sector and regional economic growth. The methods used include Location Quotient (LQ) analysis to determine the basic sectors, Shift Share to assess competitiveness, and Pearson correlation to test the relationship between the growth of the basic sectors and economic growth. The results of the study show that there are eight basic sectors during the period 2015–2024, with seven sectors classified as leading based on Shift Share analysis, except for the Electricity and Gas Supply sector. Correlation analysis revealed varying relationships between the base sector and economic growth, with most showing weak relationships. These findings confirm that the statistical superiority of a sector does not necessarily correlate with its real contribution to economic growth. Therefore, regional development planning should consider sectors that are not only statistically superior but also have competitiveness and a real impact on the local economy.